The African Church as a Mixed Bag - Sunday Agang (African Theological Journal for Church and Society)
The primary focus of this article is on the remnant nature and scope of the African church. Thus, I employ the biblical concept of a “remnant” to argue that the present demographical statistic of church growth in Africa does not translate to a concrete or tangible moral and ethical impact on society. In spite of the Southward movement of the centre of gravity of Christianity, the African church remains vulnerable like a remnant. It is in short supply of strong prophetic voices against enormous socio-economic, socio-political, and socio-religious injustices or corrupt practices at all spheres, including the church itself. The concept of a “remnant” is a key concept in the Old Testament (OT). It indicates a distinction between the “true” believers and the large bulk of outwardly religious people that does not abide by the basic requirements of being the people of God. I am using it in this article to make a comparison between the statistical evidence and the real impact on the society. Therefore, in the article I seek to argue that the African church statistics should not bluff us. Of course, looking at the multidimensional social, ethical, moral, economic, political and religious matters confronting the African continent even where the church seems to be in the majority, one cannot help but conclude that the African church is a remnant church. But, how can one convince a reader that African Christianity is a remnant faith when the current statistics is showing otherwise? For example, in 2020 the Center for the Study of Global Christianity published data that claimed, “[T]here are more than 631 million Christians that currently reside in Africa.”